1970
DOI: 10.1113/jphysiol.1970.sp009170
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the inhibition of phrenic motoneurones which occurs on stimulation of some cranial nerve afferents

Abstract: SUMMARY1. Inhibition and excitation of spontaneous phrenic nerve discharges in response to stimulation of the sinus, glossopharyngeal, aortic and superior laryngeal (SLN) nerves has been investigated in cats.2. The inhibition, in response to a single shock, had a latency of 5-10 msec and lasted for 20-40 msec; the response to SLN stimulation was the most prolonged.3. Excitation of phrenic motoneurones also occurred and was seen either before or after the end of the inhibition of the inspiratory burst and somet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

1972
1972
1993
1993

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 16 publications
3
22
0
Order By: Relevance
“…25-30 msec), an accompaying rebound excitation and a period of the reduced extent of the second inhibition lasting 20-30 msec after the first one. A similar phrenic inhibition due to disfacilitation has been noted by Biscoe and Sampson (1970b). Therefore, it would be mediated by an unidentified group of inhibitory interneurons with a self limiting mechanism.…”
Section: Discussionsupporting
confidence: 68%
“…25-30 msec), an accompaying rebound excitation and a period of the reduced extent of the second inhibition lasting 20-30 msec after the first one. A similar phrenic inhibition due to disfacilitation has been noted by Biscoe and Sampson (1970b). Therefore, it would be mediated by an unidentified group of inhibitory interneurons with a self limiting mechanism.…”
Section: Discussionsupporting
confidence: 68%
“…This may indicate that these three unrelated afferent inputs impinge on the respiratory effector mechanism at a common point. Biscoe & Sampson (1970) have demon-strated that medullary inspiratory neurones constitute at least part of the neural substrate for superior laryngeal reflexes, and have suggested that the phrenic inhibition involved disfacilitation.…”
Section: Discussionmentioning
confidence: 99%
“…On some occasions Iriuchijima & Kumada were able to evoke vagal responses by stimuli delivered during inspiration, indicating that the inspiratory refractoriness of the vagal mechanisms is not absolute. Biscoe & Sampson (1970) In all four experiments typical heart rate responses were evoked as we have described, and in two there were active inspiratory and expiratory responses to the chemoreceptor stimuli. Black & Torrance (1971) found that brief chemoreceptor stimuli effectively increase ventilation if delivered in inspiration.…”
mentioning
confidence: 99%